자녀교육에 대한 인식과 유아교육기관에 대한 요구의 이해에 기초한 교사-다문화가정 부모 관계의 구축 - 김순환; Soon Hwan Kim; 배소연; Soyoun Bae; 이영미; Youngmee Lee (다문화와 평화, 2016)
유아교사들이 다문화가정의 부모들과 바람직한 교사-부모 관계를 구축하려면 그들의 특징이나 요구를 먼저 이해하고 그에 부합하는 노력을 하는 것이 필요하다. 이에 본 연구의 목적은 한국에 거주하는 다문화가정의 어머니들이 한국에서 자녀를 교육하는 과정을 어떻게 인식하고 있으며 유아교육기관이나 교사들에게 어떤 요구를 가지고 있는지를 알아보는 것이다. 연구에는 경기와 서울지역에서 어린이집, 유치원, 복지관 등에 자녀를 보내는 102명의 다문화가정 어머니들이 참여하였으며, 자료의 수집은 연구자들이 제작한 질문지를 통하여 이루어졌다. 연구의 결과 첫째, 다문화가정의 어머니들은 자녀교육의 과정에서 많은 어려움을 느끼고 있었으며, 그 이유는 한국 사회와 학교의 제도나 문화를 잘 모르기 때문인 것으로 나타났다. 둘째, 한국의 문화를 이해하여 자녀들에게 가르치는 것, 자녀들의 한국어 발달 도와주는 것, 가정에서 자녀들의 학습이나 발달 도와주는 것 등이 가장 힘든 어려움인 것으로 나타났다. 셋째, 교사나유아교육기관에 바라는 것은 자녀에 대한 작은 문제나 의문점도 교사가 자신과 의논해 주는 것, 유아교육기관의 교직원들이 좀 더 친절히 대해 주는 것, 자녀교육에 대하여 더 많은 지원을 해주는 것 등 이었다. 마지막으로 다문화가정 어머니들의 어려움이나 요구는 어머니의 연령, 학력, 직업유무, 한국거주기간, 자녀가 재학하고 있는 기관 등에 따라 유의한 차이를 나타내고 있었다. In order for early childhood teachers to build partnerships with families from diverse cultural backgrounds, they first need to understand how the families perceive education of their child in Korean society and what they want from Korean early childhood teachers and institutions. The purpose of this study was to identify perceptions and needs of mothers with multi-cultural backgrounds on early childhood education. One hundred two mothers of young children attending different types of early childhood institutions in Seoul and Kyunggi Province participated in this study through the questionnaire developed by the researchers. Mothers with diverse cultural backgrounds experienced difficulties in the processes of education of their children due to the cultural conflict and language barriers. They want early childhood teachers to inform and consult with them about education of their children even though they have language barriers, to be friendly to them, and to provide more information and support for education of their children at home. There were significant differences in some difficulties and needs as a function of the mothers’ demographic backgrounds. Implications for early childhood teachers to build partnerships with families from diverse cultural backgrounds and for the policy makers to support these partnerships were drawn based on the results of this study.